Deepening and widening of the EU: a contradiction? - Jürgen Stehn (Rules of competition and East-West integration, 1997)
The process of European integration has reached a formerly unknown speed. The completion of the Internal Market has led to a mutual recognition or harmonization of varying standards, norms, and regulations among EU member countries. Moreover, the treaty of Maastricht widened the competences of the EU in various areas of economic policy. At the same time, the former EFTA-members Sweden, Finland, and Austria joined the European Union; the Central and Eastern European reform countries are willing to follow as soon as possible. Above all, the knocking-on-the-door of the young market-economies in Eastern Europe has raised the question, whether a widening of the integration area with countries that are lagging behind with regard to their economic development is in contradiction to a deepening of the European Union. Thus, this paper aims at discussing potential contradictions and alternative concepts of resolution. In a first part, it will be shown that the deepening of the EU has gone beyond the economic optimal degree and is, therefore, indeed in contradiction to a full membership of Central and Eastern European countries in the EU. Then, alternative concepts of an opening-up of EU-markets towards Eastern Europe will be discussed.
Keywords: 330; EU-Erweiterung; Wirtschaftsintegration; Wirtschaftsunion; Wirtschaftliche Effizienz; EU-Staaten